Hikikomori : Multidimensional understanding, assessment, and future international perspectives - Kato, Takahiro A.; Kanba, Shigenobu; Teo, Alan R. (Psychiatry and clinical neurosciences, 2019)
Hikikomori, a severe form of social withdrawal, has long been observed in Japan mainly among youth and adolescents since around the 1970s, and has been especially highlighted since the late 1990s. Moreover, hikikomori‐like cases have recently been reported in many other countries. Hikikomori negatively influences not only the individual's mental health and social participation, but also wider education and workforce stability, and as such is a novel urgent global issue. In this review, we introduce the history, definition, diagnostic evaluation, and interventions for hikikomori and also the international prevalence of hikikomori outside Japan. We propose a hypothesis regarding the globalization of hikikomori based on domestic and international perspectives. In addition, we introduce our latest assessment system for hikikomori (including the latest version of the ‘proposed diagnostic criteria of hikikomori for the future DSM/ICD diagnostic systems’) and propose therapeutic strategies, including family approaches and individualized therapies. Finally, we present future challenges that may lead to solutions for an internationalized hikikomori.